Influence of Relative Humidity on the Survival of Some Airborne Viruses - Songer, Joseph R. (1967)
A system for studying the effects of relative humidity (RH) and temperature on biological aerosols, utilizing a modified toroid for a static aerosol chamber, is described. Studies were conducted at 23 C and at three RH levels (10, 35, and 90%) with four viruses (Newcastle disease virus, infectious bovine rhinotracheitis virus, vesicular stomatitis virus, and Escherichia coli B T3 bacteriophage). Virus loss on aerosol generation was consistently lower at 90% than at 10 or 35% RH. When stored at 23 C, Newcastle disease virus and vesicular stomatitis virus survived best at 10% RH. Infectious bovine rhinotracheitis virus and E. coli B T3 bacteriophage survived storage at 23 C best at 90% RH.